MANFAAT ANTIOKSIDAN DAUN SALAM TERHADAP KADAR GLUKOSA DARAH DAN PENURUNAN APOPTOSIS NEURON DI HIPPOCAMPUS OTAK TIKUS YANG MENGALAMI DIABETES - Ayu Anggraini (Yayasan Pendidikan Medika Indonesia, 2020)
Encephalopathy diabetes is a complication of diabetes mellitus due to changes in morphology and abnormal physiological functions of the brain, due to chronic hyperglycemic conditions. Morphological changes that occur can include hippocampal brain atrophy, inflammation of nerves, changes in neurotransmitters, blood brain barrier injuries, energy metabolism disorders, and neuronal apoptosis. Increased apoptosis of these neurons occurs in the CA1 and CA3 layers of the pyramidal zone. Apoptosis of hippocampal neurons occurs through increased oxidative stress, deficits in mitochondrial function, impaired gene expression and inhibition of caspases. Antioxidants are compounds that can capture and reduce oxidative stress. Bay leaf is an antidiabetic plant that has high antioxidant properties, namely flavonoids and tannins. Flavonoids are antidiabetic compounds that reduce blood sugar levels which act as inhibitors of  glucosidase, maltase and  amylase enzymes. Flavonoids are also able to stimulate glucose uptake through GLUT-4 regulation. In addition to flavonoids, tannins are also antioxidants found in bay leaves and function as protectors of pancreatic beta cells from apoptosis due to oxidative stress. In addition, tannins can also increase levels of neurotropic factors and neuroastrocytes, injured brain, and modulate potential brain function so that can prevent neuronal apoptosis which is the main pathogenesis of diabetes.